INFLUENCE OF PINEAPPLE JUICE ADDITION WITH DIFFERENT VOLUME TO SNAKEHEAD (Channa striata) FISH SAUCE QUALITY - Isnawati '; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted at Fisheries Processing Technology and Fisheries Chemistry Laboratory, Faculty of Fisheries and Marine Science, University of Riau, on September 2014. The research was intended to evaluate the influence of pineapple juice addition with different volume to snakehead (channa striata) fish sauce quality. In this research, the fermentation processed by addition of pineapple juice with different volume (10, 15 and 20%) to snakehead fish sauce from meat weight during 6 days fermentation. The parameter analysis was observed to organoleptic (color, odor and flavor), protein content, salt content, pH, crude fiber and total of fish sauce liquid volume. The best treatment was obtained in 20% volume of pineapple juice addition (A3) with criteria: brown yellow in color of fish sauce; spesific fish sauce in odor; delicious and salty in flavor; and protein content 8.63%, salt content 8.04%, pH 5.59, crude fiber content 6.05% and volume of liquid fish sauce 12.29%.Keyword: Fish snakehead, Pineapple juice, Fish sauce and Quality